Allogenic Lymphocyte Immunotherapy for Unexplained Recurrent Spontaneous Abortion: A Meta‐Analysis. (22nd April 2016) - Liu, Zhilan; Xu, Haijing; Kang, Xiaomin; Wang, Tongfei; He, Liying; Zhao, Aimin
Abstract : Allogenic lymphocyte immunotherapy (LIT) as a treatment for unexplained recurrent spontaneous abortion (URSA) is still controversial due to the lack of enough controls to evaluate its effectiveness. Eighteen randomized, placebo‐controlled trials with LIT for URSA were included in the meta‐analysis. Live birth rates for each group were extracted, and the overall odds ratio (OR) for LIT was calculated. The success rate of treatment group was significantly higher (OR 3.74, 95% CI 3.07 ~ 4.57). LIT performed before and during pregnancy had dramatically improved the live birth rate in women with URSA (OR 4.67, 95% CI 3.70 ~ 5.90). The overall OR was 5.25 (95% CI 4.16 ~ 6.64), which supports a low dose of lymphocytes for treating URSA. Our results indicate that LIT provides a significantly beneficial effect over placebo for URSA. LIT given before and during pregnancy is superior to LIT given only before pregnancy, and the lower doses per treatment (less than 100 × 10 6 lymphocytes or 100 mL peripheral blood) achieved a better outcome.